Family Environment and Student Compliance with School Rules in Indonesian Primary Education: Evidence from a Cross-Sectional Survey - Wiratni, Ambar; Rasmi, Rasmi; Akbar, Harun (Diniyah: Jurnal Pendidikan Dasar, 2025)
Student compliance with school rules is essential for safe, orderly learning and is shaped by socialization across home and school contexts. This study examined the profile of the family environment and its relationship with compliance among Grade 5 pupils in an Indonesian public elementary school. A quantitative cross-sectional survey was conducted with 52 students selected through random sampling from a population of 105. Data were collected using two Likert-type questionnaires measuring family environment and compliance with school rules and analyzed using descriptive statistics, Pearson correlation, and simple linear regression. Most students reported a “good” family environment (55.76%) and “good” compliance (53.84%). Family environment was positively associated with compliance (r = .334, p = .015) and significantly predicted compliance (B = 0.469, t = 2.508, p = .015), explaining 11.2% of variance (R² = .112). The findings indicate that supportive and structured home conditions contribute modestly to rule-following, while substantial variability likely reflects school climate, peer dynamics, and individual self-regulation. Strengthening home–school alignment may support more consistent student discipline. Keywords: family environment; student compliance; school rules; elementary school; parental monitoring